Voice over IP networks quality of service, pricing and security - Verma, Pramode K.; Wang, Ling Dr.; SpringerLink (Online service). (Berlin Springer, 2011)
This book addresses three important issues in VoIP networks: Quality of Service, pricing and security. In addressing Quality of Service (QoS), it introduces the notion of delay not exceeding an upper limit, termed the bounded delay, to measure the Quality of Service in VoIP networks. Queuing models are introduced to measure performance in terms of bounded delays. Closed form solutions relating the impact of bounding delays on throughput of VoIP traffic are provided. Traffic that exceeds the delay threshold is treated as lost throughput. The results addressed can be used in scaling resources in a VoIP network for different thresholds of acceptable delays. Both single and multiple switching points are addressed. The same notion and analysis are also applied on jitter, another important indicator of the VoIP QoS This book also develops a pricing model based on the Quality of Service provided in VoIP networks. It presents the impact of quality of VoIP service demanded by the customer on the transmission resources required by the network using an analytical approach. In addition, it extends and applies the delay throughput analysis developed for VoIP networks in assessing the impact of risks constituted by a number of transportation channels, where the risk associated with each channel can be quantified by a known distribution. Finally, the book explores areas for future research that can be built on the foundation of research presented.
Introduction -- Voice over Internet Protocol -- Traffic Characterization -- Impact of Bounded Delays on Resource Consumption in Packet Switched Networks with M/M/1 Traffic -- Impact of Bounded Delay on Resource Consumption-M/D/1 Model -- Impact of Bounded Jitter on Resource Consumption in Multi-hop Networks -- Cost and Quality in Packet Switched Networks: An Abstract Approach -- Cumulative Impact of Inhomogeneous Channels on Risk -- A Network Based Authentication Scheme for VoIP -- Conclusions and Future Work.
Electronic reproduction.
Keywords: Internet telephony; TCP/IP (Computer network protocol).; Digital telephone systems; Computer networks; Data transmission systems; Electronic books